Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Problem Based Learning di Kelas IV SD - Mutiara, Sri; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2017)
This study aims to describe an increase in student learning outcomes in integrated thematic learning with a problem based learning model in grade IV of Indarung Elementary School. The sample in this study were all students of grade IV of SD Negeri 20 Indarung as many as 20 students. The results of the study on teacher activities from cycle I were 85%, increasing to 95% in cycle II. The increase in student activity from the first cycle is 87.5%, increasing to 95% by the second cycle. While the learning outcomes aspects of students' attitudes in the first cycle of the value of 3.00 increased to 3.66 in the second cycle, the knowledge aspect in the first cycle which achieved a value of 2.33 increased to 3.66 in the second cycle and the skill aspects in the first cycle that achieved value 3.00 increased to 3.66 in the second cycle, so the results of the study said there was an increase in better learning outcomes in integrated thematic learning using a problem based learning model in grade IV of SD 20 Indarung.